Testing the TEBOTS model in self-threatening situations: The role of narratives in the face of ostracism and mortality - Rieger, Diana; Schneider, Frank M. (Frontiers in Communication, 2022)
Previous research on the TEBOTS model has demonstrated that narratives are sought after more often in times of depletion. This study aimed at expanding this idea by applying the TEBOTS model to self-threatening states and testing whether these also lead to an increased engagement with narratives. In a 3(Threat: mortality salience vs. ostracism vs. control) × 2(Review of the narrative: positive vs. negative) online experiment (N=228), we tested whether self-threats and the expectation of the narrative led to increased levels of entertainment experience. Further, it was tested whether narratives can serve as a coping instrument during self-threats by facilitating self-serving attributions. Results demonstrated that self-threats and a positive review indeed increased the entertainment experience. Further, narratives could support buffering from existential threats. These findings are discussed in light of the TEBOTS model and its application in the context of self-threats.